Penerapan P5 dalam Membentuk Karakter Kewirausahaan Melalui Kegiatan Festival Food di SDIT Al Hikmah Depok - Ramdhani, Rahmat; Kurniawati , Hartin (Institut Agama Islam Sahid (INAIS) Bogor, 2023)
The purpose of this study is to determine the effectiveness and efficiency of the application of entrepreneurial character values, teachers can help students apply creative values so that they are able to produce products with high selling power. This research is a qualitative research